Central African Republic : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the 2005 Article IV Consultation on the Central African Republic (CAR) highlights economic developments and performance. Revenue performance was disappointing, and there were sizable expenditure overruns, particularly on the wage bill. The authorities and IMF staff agreed on the importance of raising government revenue to ensure that sufficient resources are available for basic government functions. Key reforms will include efforts to combat fraud in customs and improve domestic tax administration through increased controls and verification procedures.